2021
DOI: 10.1111/jocs.15652
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral thoracoscopic sympathectomy for cardiac denervation in pediatric population: Does Kuntz nerve cauterization have an impact on success?

Abstract: Introduction Cardiac sympathetic denervation (CSD) is an effective procedure for the treatment of inherited channelopathies. Left CSD has traditionally been recommended as neuromodulation to prevent arrhythmia episodes; however, it is thought that bilateral sympathectomy in combination with Kuntz ablation may have additional effects effective due to the anatomical variability of preganglionic sympathetic fibers. The aim of the study was to share our single‐center clinical experience with bilateral thoracoscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…One study demonstrated a 70% success rate for BCSD in managing refractory VAs [ 10 ]. Multiple studies have suggested that BCSD may have a stronger antiarrhythmic effect than LCSD [ 2 , 11 ]. A case series documented a 90% complete resolution of ICD shocks following BCSD [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study demonstrated a 70% success rate for BCSD in managing refractory VAs [ 10 ]. Multiple studies have suggested that BCSD may have a stronger antiarrhythmic effect than LCSD [ 2 , 11 ]. A case series documented a 90% complete resolution of ICD shocks following BCSD [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…If patients are intolerant to these drugs or if VAs persist despite medication, catheter ablation and the insertion of implantable cardioverter defibrillators (ICD) may be considered. For arrhythmias that remain unmanageable with standard treatments, cardiac sympathetic denervation could serve as an additional therapeutic strategy [ 1 - 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…While RCSD alone remains an unconventional therapeutic option, bilateral cardiac sympathetic denervation has shown promise within small series in the treatment of refractory ventricular arrhythmia across a range of conditions including ischaemic and nonischaemic cardiomyopathy, arrhythmogenic right ventricular cardiomyopathy (ARVC) and Chagas disease,12–16 with a randomised trial planned 17. However, there is a paucity of evidence for outcomes in patients with CPVT.…”
Section: Discussionmentioning
confidence: 99%
“…2 Typically, a stellate ganglion block (SGB) is utilized, but this procedure remains technically challenging and can cause rare but dangerous side effects. 3 The proximal intercostal block has been suggested as an alternative technique that is conducive to continuous blockade via catheters while maintaining a favorable safety profile. 4 This report describes the elective, novel, effective, and safe use of bilateral continuous proximal intercostal blocks to provide therapeutic sympathetic blockade in CPVT.…”
mentioning
confidence: 99%